Controlled Release Of Nutrients From Coconut Water-Based Hydrogels - Muthu, Vikneswaran (2019)
Studies have proven that coconut water could replenish nutrients and rehydrate during physical exercise. Nutrients in coconut water, i.e. sugars and electrolytes, can be easily and rapidly absorbed by our body. By designing coconut water into a controlled-release system, it can provide nutrients release to the body in a sustained manner. Therefore, the aim of this study is to develop a coconut water-based energy gel with in situ gelling property. Coconut water-based hydrogel made of gellan and xanthan gelling polymers was formulated as a base to develop the energy gel. Hydrogel formulation with mixture of 0.7% gellan and 0.3% xanthan showed in situ gelling system that was able to retain over 1 h period in dissolution test before completely dissolved. During in vitro release study, the trend of release profile showed that the hydrogel had the ability to sustain nutrients release over a period of 1 h. After 75 min, the release trend was static, indicating that all the sugars were released from the hydrogel. Since the developed hydrogel does not provide sufficient nutrients, i.e. carbohydrate and sodium, required for exercise, maltodextrin and sodium chloride were added to produce coconut water-based energy gel. The in vitro test on the energy gel showed that it is capable fo releasing the nutrients in a controlled manner. The linear trend of cumulative percentage showed sustained nutrient release from the energy gel. The effect of gelling agents and coconut water being added to the energy gel was also examined using the same in vitro study.